Inheritance main etiological factor of mental abnormality and degeneration and certain forms of crime prevention and eugenics - Fosalba, Rafael G. (1929)
The physiological heredity, transmission from parent to child, through several generations, certain physical and moral character, has been recognized since ancient times; but as new research methods have enabled advanced the study of biological science, theories have multiplied together to explain the phenomena of life.